The Pauline effect: the use of the Pauline epistles by early Christian writers - Strawbridge, Jennifer R. (Studies of the Bible and its reception, 2015)
print_cont_9783110437706_Strawbridge_I-IV -- print_cont_9783110437706_Strawbridge.